2015
DOI: 10.14748/ssm.v47i2.1145
|View full text |Cite
|
Sign up to set email alerts
|

Experimental models of metabolic syndrome in rats

Abstract: Metabolic syndrome (MS) is a disorder comprising central obesity, dyslipidemia, raised blood pressure, insulin resistance. The aim of the present study was to develop a cheap, easy and reproducible rat model of MS. 36 male Wistar rats were divided in 3 groups: a control group (C) receiving regular rat chow diet, a high-fat (HF) group receiving lard enriched rat chow and a high-fat high-fructose (HFHF) group receiving lard and fructose enriched rat chow. HF and HFHF groups had also 10% fructose in their drinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 31 publications
2
26
0
6
Order By: Relevance
“…Our results were in line with other literature reports, whereby the consumption of HCHF diet decreased rates of glucose clearance in MetS rats and those animals were experiencing dyslipidemia [21,[25][26][27][28]. Apart from HCHF diet, an excess of dietary fructose [37,38], fat [39,40] or combination of fructose and fat [41,42] has been widely reported to contribute for insulin resistance and dyslipidemia.…”
Section: Discussionsupporting
confidence: 93%
“…Our results were in line with other literature reports, whereby the consumption of HCHF diet decreased rates of glucose clearance in MetS rats and those animals were experiencing dyslipidemia [21,[25][26][27][28]. Apart from HCHF diet, an excess of dietary fructose [37,38], fat [39,40] or combination of fructose and fat [41,42] has been widely reported to contribute for insulin resistance and dyslipidemia.…”
Section: Discussionsupporting
confidence: 93%
“…Feeding HFHF diet given rise to a significant increase in the serum levels of blood glucose, total lipids, total cholesterol, VLDL-c, LDL-c and TAG with a significant reduction in both serum insulin and HDL-c which confirms the state of T2DM. Gancheva et al [29] and López et al [45] reported that, feeding HFHF diet for 12 weeks resulted in induction of metabolic syndrome and with elevated serum glucose and lipid profile and a reduction in serum insulin and HDL-c.…”
Section: Discussionmentioning
confidence: 99%
“…The caloric intake would be 800 kcal per 100 g food, of which 60% provided by the lard and 17% by the fructose supplementary to the typical rat foodstuff for one month. After that, the blood glucose level was measured [29], and rats with blood glucose more than 200mg/dl were taken as obese-diabetic group whereas that less than 200mg/dl considered as obese non-diabetic group. The rats were then subdivided into different groups and received different treatments for 4 weeks as follow: Group 2 (G2): obese non-diabetic didn't take any medication,group 3 (G3): obese-diabetic didn't take any medication.…”
Section: Experimental Designmentioning
confidence: 99%
“…This model was planned to mimic nearly the cafeteria diets (CAF) which essentially contain high caloric value [5]. The body weight and blood glucose were taken once weekly for 12 wk [9].…”
Section: Formulation Of Hfhf Dietmentioning
confidence: 99%
“…MicroRNA-146a is involved in the pathogenesis of autoimmune diseases and several types of cancer [3]. In addition, miRNA-146a can be involved in the pathology of inflammatory degenerative diseases in human, such as prion disease [6], Alzheimer's disease [7,8] and epilepsy [9]. In ischemic stroke the increased microRNA-126 in endothelial cells can promote angiogenesis, and attenuate vascular dysfunction in diabetics [10].…”
Section: Introductionmentioning
confidence: 99%